Doxing in Cyberspace Based on Law No. 27 of 2022 on Personal Data Protection - Wahyudi, Endik; Adilah, Daffa (Jurnal Idea Hukum, 2024)
One of the negative impacts of technological advancement is the rise of cybercrimes, including doxing. Doxing refers to the act of publicly disclosing someone's data online without permission, with the intention to intimidate or damage their reputation. To address this issue, Law No. 27 of 2022 on Personal Data Protection was enacted, although the law still has gaps, particularly in relation to doxing acts. This study aims to examine how doxing is regulated under this law and the sanctions imposed. The method used in this study is a normative juridical approach and the Statute Approach. The results show that Law No. 27 of 2022 on Personal Data Protection can effectively handle the unlawful collection and disclosure of personal data. However, it is still inadequate in addressing the malicious intent behind doxing itself. The lack of this element creates a legal gap in the law, as judges may have to rely on legal interpretation principles. However, this approach must be balanced with the principle of legality, which requires that laws be unambiguous to avoid arbitrary punishment. Another area for improvement in the law is the absence of a minimum penalty for violators. Although the law stipulates a maximum penalty, more than a specific minimum penalty is needed to allow for a wide range of sentences, which may lead to inconsistencies in sentencing. By incorporating a specific minimum penalty, the law could provide more effective deterrence, ensure consistent punishment, and restore a sense of justice for victims and society.Keywords: cyberspace; doxing; personal data protection